Formation and development of the architecture of the Central Bank of Manchukuo - Антон Ким (Проект Байкал, 2022)
The article is devoted to the analysis of the development of the architecture of the Central Bank of Manchukuo in 1932–1945. The prerequisites for the development of the architecture of banking institutions in the region are considered. The key influence of the Japanese architectural school, which manifested itself to the greatest extent in the 1930s after the formation of Manchukuo, is revealed. The building of the head office of the Central Bank in Changchun, which incorporated the most advanced developments and approaches to the construction of such facilities, is described in detail. In addition, the variations of numerous branches located in other cities of the country are reviewed and the use of a single corporate style and stylistic ranking of objects depending on the location is revealed. The article analyzes the change of stylistic preferences from neoclassicism to functionalism, in which the compositional and planning structure remained unchanged, while the decoration underwent changes depending on the place and time of construction.